THE EFFECT OF SERVICE QUALITY AND TRUST ON CUSTOMER SATISFACTION AND LOYALTY AT PT. AGUNG TOYOTA HARAPAN RAYA PEKANBARU - Armawi Fauzi Nasution; Surya Safari SD; Astri Ayu Purwati; Harry Patuan Panjaitan (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This study aims to analyze the effect of service quality and trust on customer satisfaction and loyalty at PT. Agung Toyota Harapan Raya Pekanbaru. This research is a quantitative research by distributing questionnaires to respondents. The populations in this study were customers who bought a car and used regular service at PT. Agung Toyota Harapan Raya with a total of 1,478 people. The sample calculation technique used the slovin formula, so the number of samples in this study was 100 people. The sample selection method in this study used the incidental technique, namely the determination of the sample based on chance. The data analysis deployed Structural Equation Modeling (SEM) utilizing SmartPLS 3.0 application. The results of this study indicate that service quality has a positive but not significant effect on customer satisfaction, trust has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer loyalty, trust has a positive but not significant effect on customer loyalty and customer satisfaction has a positive and significant effect on customer loyalty.